Optimised and Rapid Pre-clinical Screening in the SOD1G93A Transgenic Mouse Model of Amyotrophic Lateral Sclerosis (ALS) - Mead, Richard J.; Bennett, Ellen J.; Kennerley, Aneurin J.; Sharp, Paul; Sunyach, Claire; Kasher, Paul; Berwick, Jason; Pettmann, Brigitte; Battaglia, Guiseppe; Azzouz, Mimoun; Grierson, Andrew; Shaw, Pamela J. (PLOS ONE, 2011)
The human SOD1G93A transgenic mouse has been used extensively since its development in 1994 as a model for amyotrophic lateral sclerosis (ALS). In that time, a great many insights into the toxicity of mutant SOD1 have been gained using this and other mutant SOD transgenic mouse models. They all demonstrate a selective toxicity towards motor neurons and in some cases features of the pathology seen in the human disease. These models have two major drawbacks. Firstly the generation of robust preclinical data in these models has been highlighted as an area for concern. Secondly, the amount of time required for a single preclinical experiment in these models (3–4 months) is a hurdle to the development of new therapies. We have developed an inbred C57BL/6 mouse line from the original mixed background (SJLxC57BL/6) SOD1G93A transgenic line and show here that the disease course is remarkably consistent and much less prone to background noise, enabling reduced numbers of mice for testing of therapeutics. Secondly we have identified very early readouts showing a large decline in motor function compared to normal mice. This loss of motor function has allowed us to develop an early, sensitive and rapid screening protocol for the initial phases of denervation of muscle fibers, observed in this model. We describe multiple, quantitative readouts of motor function that can be used to interrogate this early mechanism. Such an approach will increase throughput for reduced costs, whilst reducing the severity of the experimental procedures involved.